2000
DOI: 10.1007/s007870070026
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in children after the military operation "Anfal" in Iraqi Kurdistan

Abstract: Five years after the military operation "Anfal" in Iraqi Kurdistan, 45 families were randomly selected among the survivors in two displacement camps. The Posttraumatic Stress Symptoms for Children (PTSS-C) and the Harvard Trauma Questionnaire (HTQ) were administered to the oldest child and the caregiver in each family, respectively. Posttraumatic stress disorder (PTSD) was reported in 87% of children and 60% of their caregivers. While childhood PTSD was only significantly predicted by child trauma score and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 0 publications
4
71
1
Order By: Relevance
“…For example, Carrion et al [2002] found that children who met subthreshold criteria did not differ significantly from children meeting all three cluster criteria. Some researchers found a highfunctioning level among traumatized children in spite of PTSD [Ahmad et al, 2000;Sack et al, 1995], thus suggesting this might be a characteristic of childhood PTSD, supporting the necessity of child-specific criteria for this disorder.…”
Section: Ptsd In Children Diagnostic Considerationsmentioning
confidence: 97%
“…For example, Carrion et al [2002] found that children who met subthreshold criteria did not differ significantly from children meeting all three cluster criteria. Some researchers found a highfunctioning level among traumatized children in spite of PTSD [Ahmad et al, 2000;Sack et al, 1995], thus suggesting this might be a characteristic of childhood PTSD, supporting the necessity of child-specific criteria for this disorder.…”
Section: Ptsd In Children Diagnostic Considerationsmentioning
confidence: 97%
“…High rates of PTSD have been found in studies of children living in conflict areas [19,30,35]. Similar to patterns in adults [6] chronic post-trauma symptoms persist in a substantial sub-group of children and can severely interfere with functioning [20,50,51].…”
Section: Discussionmentioning
confidence: 82%
“…In terms of pre-trauma factors, there have been contradictory findings from studies in relation to age [23,[29][30][31]. Trickey and colleagues [5] reported that younger age is largely unrelated to whether a young person develops PTSD but moderator analysis discovered that there was a statistically significant stronger relationship when the trauma was unintentional although the population effect size remained non-significant regardless of whether the trauma was intentional or non-intentional.…”
Section: The Omagh Bombingmentioning
confidence: 99%
“…The majority of studies that have been done have addressed eastern European populations, particularly Bosnians. Studies of refugee children conducted outside the war zone are most common [14][15][16][17][18][19][20][21]. However, assessments have also been conducted in war zones including Bosnia [22][23][24], Kosovo [25], Croatia [26], and Iraq [27].…”
Section: Warmentioning
confidence: 99%